Rights of Arrested Person and How to Protect them in the Libyan Law - Sherif, Abdallah Abdusalam; Haj Ibrahim, Badruddin (Journal of Economic, Administrative and Legal Sciences, 2019)
This study deals with the rights of those arrested and their protection in Libyan legislation. The arrest of persons is one of the most important and most dangerous measures against freedom. It affects one of the most important human rights, namely, the right to freedom. Which is legally competent to carry out the investigation, taking into account its detention in the places designated for that purpose. The problem of the legal texts in the Libyan criminal law focuses on the recognition of the rights of those arrested, protecting them against any unlawful interference with them, or exaggeration and strictness in restricting them. What is their compatibility with or contradictions with the basic provisions of the Libyan Constitution? What is the way to remove and raise this discrepancy that exists? In this study, the study relied on the analytical descriptive approach to identify the rights of those arrested, as well as the means established by the law to guarantee these rights from any abuse by the competent authorities in this dangerous procedure, by studying and analyzing the legal texts and relevant judicial decisions. The Libyan law, to identify the rights of those arrested and the means of protecting them, and to assess the position of the Libyan legislator of all this. This study concluded with a number of results: The right of defense is an inherent right of the accused from the moment that he is charged with a crime. This right remains valid throughout the investigation and trial stage. However, we did not find explicit provisions in Libyan law the right of the accused to have access to a lawyer during his arrest or even during the investigative and forensic procedures carried out by the judicial ombudsman. The matter was left without an explicit statement confirming the right of the accused to seek legal assistance or to deny this right. There is no explicit provision in the Libyan law that the arrested defendant has the right to remain silent in the case of arrest, and there is no text in return that requires him to give his testimony before the investigative and investigative bodies. So, there is a difference about recognizing this right.